Myths Around Stroke and Failures of Broadcasts Preventive Communication: Lived Experiences of Stroke Patients and Survivors in Nigeria - Abubakar, Ibrahim Y.; Saheed, Olayinka; Adisa, Rasaq M.; Udende, Patrick; Yusuf, Sholola A.; Abdulrauf-Salau, Aisha; La’aro, Abdulkadir (Unisia, 2023)
Although stroke is regarded as the second leading cause of death in the world, it is less discussed in the media as such awareness. The study, which was anchored on the Health Belief Model, adopted a qualitative research design, while the interview was employed as the data gathering method from informants purposely selected from the Stroke Rehabilitation Center, Osogbo, Nigeria. Thematic Analysis, with the aid of NVivo 10 Software, was adopted to carry out the analysis. The findings of the study revealed that stroke patients and survivors expressed disappointment with the low attention given to the coverage of the incidence of stroke in Nigeria, despite many myths surrounding it. The challenges encountered by stroke patients and survivors include inadequate stroke information, especially from broadcast media, and lack of awareness. The study recommended that journalists should be more proactive in reporting and discussing stroke, especially regarding symptoms, causes, and management, as a large number of victims exist in developing countries where there is a high prevalence of stroke. It also recommends that the government equip public hospitals with tools and personnel to manage all forms of paralysis.